The Minimum Income Standard as a benchmark of a 'participatory social minimum'. (28th February 2018) - Davis, Abigail; Hirsch, Donald; Padley, Matt
Abstract : The Minimum Income Standard (MIS), a method for constructing minimum household budgets based on public consensus, helps to operationalise Townsend's concept of a 'participatory social minimum'. Since 2008 MIS has tracked changes in the contents and cost of minimum baskets of goods and services. The article reflects on aspects of this research: the living standard that MIS represents, how consensus is reached and its record of providing consistent results over time. Understanding these features allows policy makers, practitioners and analysts to use the results of MIS appropriately, alongside other research, to benchmark the success of measures to promote adequate incomes.